Institutionalizing Non-Domination Principle in Anti-Corruption Reform of Indonesia’s Energy Governance - Alfin Dwi Novemyanto; Rismawati Nur (Dialogia Iuridica, 2025)
Corruption in energy governance in Indonesia reveals an imbalance of power between bureaucratic actors, corporations, and the public, giving rise to a form of structural domination that is difficult to overcome through conventional administrative approaches. This study offers a theoretical contribution by applying the principle of non-domination in republicanism theory as an analytical framework to understand the roots of this domination and assess the weaknesses in institutional design that enable corrupt practices, particularly in oil procurement and imports. Through a normative juridical method combined with doctrinal analysis and a case study of corruption at Pertamina during the 2018–2023 period, this study finds that corruption not only causes fiscal losses but also reduces the state's capacity to regulate the supply chain, deepens dependence on private and foreign actors, and weakens economic sovereignty as intended by Article 33 of the 1945 Constitution. The results of the study identify three institutional mechanisms that can operationalize the principle of non-domination in energy governance, namely procedural openness, independence of supervision and management of state-owned enterprises, and public objection mechanisms to review energy policies. These findings emphasize that anti-corruption reform requires a reconstruction of power structures, not just increased administrative compliance. This research contributes to the literature by combining republicanism theory with energy law and anti-corruption studies, while also opening space for further research on the application of the non-domination framework in other energy sub-sectors and in the governance of strategic resources in developing countries.